2011
DOI: 10.1161/strokeaha.110.600023
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Stroke Due to a Novel Voltage Sensor Mutation in Ca v 2.1 Responds to Verapamil

Abstract: Background and Purpose— Familial hemiplegic migraine is characterized by recurrent migraine, hemiparesis, and ataxia. Causes may be mutations in calcium and sodium channels or in a subunit of the Na/K-ATPse. Migraine treatment with calcium channel blockers was only successful in some patients. Summary of Case— We describe a 6-year-old girl with recurrent ischemic strokes after minor head trauma associated with seizures, hemiparesis, fever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…However, this is the third reported case of suspected hemiplegic migraine where the patient regained full motor function during verapamil infusion [6, 7]. At the time of verapamil infusion, 1 h 32 min had elapsed since the end of rtPA infusion – with no remarkable gain of motor function.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this is the third reported case of suspected hemiplegic migraine where the patient regained full motor function during verapamil infusion [6, 7]. At the time of verapamil infusion, 1 h 32 min had elapsed since the end of rtPA infusion – with no remarkable gain of motor function.…”
Section: Discussionmentioning
confidence: 96%
“…Of the 3 previous reports, 2 showed resolution of hemiplegia [6, 7]. In the third case, the patient had resolution of headache but persistent hemiparesis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, single channel recording showed that the mutations enhanced the open probability of the Ca V 2.1 channels and shifted the activation gating of the channel to more negative voltages, allowing increased Ca 2+ influx at more negative membrane potentials in cerebellar neurons [33,34] . Common treatments with Ca 2+ channel blockers, such as verapamil, is effective in some FHM1 patients, carrying the CACNA1A mutations due to decreased open probability of P/Q-type Ca V 2.1 channels and reduced Ca 2+ influx [35] . Consistent with reports of increased open-channel probability [32,33] , a recent study showed that FHM-1 missense mutants of the C-terminus in Ca V 2.1 subunit, R192Q and S218L, permitted a larger Ca 2+ influx during action potentials than the wildtype channels in the cerebellar neurons [36] .…”
Section: +mentioning
confidence: 99%
“…Since the first CACNA1A disease-causing variants were described in EA2 7 , over 80 EA2 alterations have been reported in the gene 3 . Several other neurological disorders are caused by pathogenic variants in CACNA1A , including familial hemiplegic migraine (FHM1, MIM #301011) and spinocerebellar ataxia type 6 (SCA6, MIM #183086), and the gene has also been related to other hemiplegic migraine (HM)-associated phenotypes like alternating hemiplegia of childhood 8 , acute striatal necrosis 9 , hemiplegia-hemiconvulsion-epilepsy 10 or recurrent ischemic stroke 11 .…”
Section: Introductionmentioning
confidence: 99%